Achievement and Improvement of Junior High School Students' Numeracy Skills through a Realistic Mathematics Education Approach - Timo, Maria Elisabeth; Son, Aloisius Loka; Salsinha, Cecilia Novianti (Brillo Journal, 2025)
The results of a survey conducted by PISA show that the achievement of students' numeracy skills in Indonesia is relatively low, with many students having difficulty applying basic mathematical concepts in everyday life. This condition requires 21st-century learning to not only focus on mastering content, but also on developing numeracy skills that are integrated into various subjects. Therefore, this study was conducted to determine the achievement and improvement of numeracy skills of grade VIII junior high school (JHS) students through the realistic mathematics education (RME) approach. The research method used is a quantitative method with a quasi-experimental research type, which was conducted at a junior high school in North Central Timor Regency. The instrument used was a numeracy ability test sheet. The data obtained were analyzed using the t-test. The results of the study showed that the achievement and improvement of numeracy skills of grade VIII junior high school students who studied through RME approach were higher than students who studied without the RME approach. Specifically, students taught with the RME approach showed better understanding in solving contextual problems and applying mathematical concepts, and experienced a more significant increase in scores between the pretest and posttest. It is recommended for junior high school mathematics teachers to implement RME to facilitate students' numeracy skills. It is recommended for junior high school mathematics teachers to implement RME to facilitate students' numeracy skills.